Effects of Localized Heating on Pain, Skin Perfusion, and Wound Healing After Lumbar Decompression. Issue 5 (October 2020) - Kim, Jeoung Hee; Shin, Yong Soon
Abstract : ABSTRACT: BACKGROUND: Current evidence regarding the effectiveness and safety of localized heating after spinal surgery for pain, peripheral tissue perfusion, and wound healing is conflicting. METHODS: This study was a prospective, single-blind, randomized controlled trial; 58 adult patients were randomized to an experimental group or a control group after spinal decompression surgery. All participants received localized cooling on postoperative days 1 and 2. The experimental group received localized heating at the surgical wound on postoperative days 3 and 4, and the control group kept normothermia without localized heating. Outcome variables were evaluated 1 hour after surgery and on day 4. RESULTS: Postoperative pain was significantly lower in the experimental versus control group (13.8 vs 23.0, P = .01). Skin perfusion was better in the experimental versus control group (4.7 vs 2.8, P = .001). There was no statistically significant difference in the wound healing status between the groups. CONCLUSION: Localized heating can effectively relieve postoperative pain and improve skin perfusion. These results suggest that localized heating tailored to the wound healing process may be beneficial for patients undergoing spinal surgery. Abstract : Supplemental digital content is available in the text.